Predictors of Influenza Vaccination in Early Rheumatoid Arthritis 2017‐2021: Results From the Canadian Early Arthritis Cohort. Issue 7 (29th March 2022) - Ta, Viviane; Schieir, Orit; Valois, Marie‐France; Colmegna, Ines; Hitchon, Carol; Bessette, Louis; Hazlewood, Glen; Thorne, Carter; Pope, Janet; Boire, Gilles; Tin, Diane; Keystone, Edward C.; et al.
Abstract : Objective: Adults with rheumatoid arthritis (RA) are at a higher risk for infections, including influenza and related complications. We identified influenza vaccination coverage in adults newly diagnosed with RA and examined sociodemographic RA characteristics and attitudes associated with vaccination. Methods: We used data from patients enrolled in the Canadian Early Arthritis Cohort between September 2017 and February 2021. At enrollment, participants reported their vaccination status in the previous year and completed the Beliefs About Medicines Questionnaire (BMQ). Clinical data were obtained from medical records. Logistic regression was used to identify predictors of vaccination in the year after RA diagnosis. Results: The baseline analytic sample of 431 patients were mostly White (80%) women (67%) with a mean age of 56 (SD 14) years. Prediagnosis, influenza vaccine coverage was 38%, increasing to 46% post diagnosis in the longitudinal sample (n = 229). Participants with previous influenza vaccination (odds ratio [OR] 15.33; 95% confidence interval [CI] 6.37‐36.90), on biologics or JAKs (OR 5.42; 95% CI 1.72‐17.03), and with a higher change in BMQ Necessity‐Concerns Differential scores (OR 1.08; 95% CI 1.02‐1.15) had greater odds, whereas women (OR 0.32; 95% CI 0.14‐0.71), participants with a non‐White racial background (OR 0.13; 95% CI 0.04‐0.51), and participants currently smoking (OR 0.09; 95% CI 0.02‐0.37) had lower odds of influenza vaccine coverage. Conclusion: Influenza vaccination coverage in patients with early RA remains below national targets in adults living with a chronic condition. Discussing vaccine history and medication attitudes at initial clinic visits with new patients with RA may enhance vaccine acceptance and uptake.